Neonatal Microbiome, Intestinal Inflammation, and Necrotizing Enterocolitis - Kathryn Y. Burge; Troy A. Markel (Microorganisms, 2022)
Necrotizing enterocolitis (NEC), the most common gastrointestinal emergency in the neonatal intensive care unit (NICU), is a leading cause of preterm infant morbidity and mortality [...]